Cross-Culture Communication Management: Difference And Building at PT Las Coal Mandiri - Nadya Sukma Choirunnisa; Iwan Joko Prasetyo; Nurannafi Farni Syam Maella; Redi Panuju (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study discusses a conceptual study of cross-cultural communication practices at PT Laz Coal Mandiri. This study was designed to explore how the Company deals with existing problems related to communication and information transfer between the Company's staff in the presence of differences in individual cultural backgrounds and other individuals. In this study, researchers compiled using qualitative research methods using the Library's review method through books, scientific articles, journals, and other publications. The results obtained in this study show that cultural differences have a significant influence on communication between groups at PT Laz Coal Mandiri. Negotiating between multicultural groups at PT Laz Coal Mandiri is often complicated and requires a thorough understanding of each party's cultural norms. In addition, it also explores how collaboration can be built between teams from different cultures at PT Laz Coal Mandiri. It was concluded that intercultural communication management at PT Laz Coal Mandiri is essential to establishing effective collaboration between multicultural teams.